Conﬁdence Level of Interns for Performing Root Canal Treatment: A Descriptive Cross-Sectional Study - Rupam Tripathi,; Nisha Acharya,; Sirjana Dahal,; Jwolan Khadka,; Pujan Kranti Kayastha,; Manisha Nepal, (Journal of Universal College of Medical Sciences, 2023)
INTRODUCTION Due to various anatomic complexities within root canals, endodontic treatment sometimes become a difﬁcult dental procedure to perform even for the specialist. Many dental students consider endodontics to be complicated and stressful. However, dental students must be competent enough to manage speciﬁc clinical procedures. This study was conducted to assess the conﬁdence level of dental interns in performing endodontic treatment. MATERIAL AND METHODS A descriptive cross-sectional study was conducted among dental interns of Nepal from December 2021 to January 2022. Ethical clearance was obtained from institutional review committee of UCMS (UCMS/IRC/105/20). Census method was used for selecting study participants. An online questionnaire was distributed that covered demographic details and the interns’ conﬁdence level regarding endodontic treatment. Participants were asked to indicate their self conﬁdence level by Likert scoring system ranging between 1-5. The data were analyzed in Statistical Package for Social Sciences (SPSS) version 20 software. RESULTS Majority of dental interns were conﬁdent in establishing successful communication with pa¬tients during diagnosis, root canal treatment and irrigation. Placement of rubber dam, root canal shaping and management of ﬂare-ups were the procedures in which dental interns reported the lowest conﬁdence (2.21±1.047, 2.65±.974, 3.31±.780). Lowest conﬁdence was reported in the treatment of maxillary followed by mandibular molars (2.72±.821 and 3.14± .959). They also reported the lowest conﬁdence in teeth with root resorptions, immature apices and re-treatment cases (2.39±.842, 2.49±.836 and 2.52±.981). CONCLUSION Dental interns reported conﬁdence in carrying out basic endodontic skills but lower conﬁdence in challenging and complicated procedures. Further training should be emphasized in management of such situations.